American Orientalism: A Historical Background - Awad Ibrahim, Abdul Sattar (Opción, 2019)
This research paper is intended to present a historical background about American orientalism. It concentrates on those aspects which have obliged the Occident to explore the Orient, shedding light on political, social, econom- ic,and cultural factors to be examined in this regard. It also sheds light on the American tendency to monopolize studies on orientalism in an attempt to be independent of European studies in this respect. Besides, the research paper unfolds the American interest in the Orient in general and in the Arabic and Islamic world in particular and the reasons that have made America examine them thoroughly on many and various levels. Furthermore, there will be a clear account about those bright and glorious aspects of which the Arab and Islamic world has been proud of and by which the Occident has been fascinat- ed and influenced. This research paper quotes those signs of the Holy Quran which show the Occident’s hatred and envy towards the Arab Muslims and which show how its civilization will one day collapse and be transferred to other nations and countries.